Cost-Effectiveness Analysis of Rubella Screening Strategies using Electronic Medical Records - Straub, Heather L.; Antoniewicz, Leah W.; Riggs, John W.; Plunkett, Beth A.; Hollier, Lisa M. (American Journal of Perinatology, 2013)
Objective The redundancy of routine laboratory tests in medicine has become increasingly more apparent in the age of electronic medical records (EMRs). The purpose of this study was to determine whether targeted screening strategies are more cost-effective than the current standard of universal screening of pregnant women for immunity to rubella.Study Design A decision analysis model was used to evaluate three strategies: universal screening, screening if a previous titer was not available, and use of an “alert” in the EMR to prompt screening. Cost, probability, and utility values were derived from the literature and institutional data from Lyndon B. Johnson General Hospital. One-way sensitivity analyses were performed on all cost and probability values.Results The strategy of an EMR alert was most cost-effective, with a cost of $0.27 per quality-adjusted life years (QALY). The model was robust to all costs and probability values over their respective ranges.Conclusions Although all strategies were cost-effective compared with traditional industry benchmarks of $50,000/QALY, the EMR alert strategy is most cost-effective. Implementing an EMR alert may lead to a more cost-effective approach to prenatal evaluation of rubella immunity.
Keywords: cost-effectiveness; electronic medical record; rubella screening; vaccination; decision analysis